2013
DOI: 10.1007/s13555-013-0040-z
|View full text |Cite
|
Sign up to set email alerts
|

The Costs of Psoriasis Medications

Abstract: IntroductionPsoriasis is a chronic disease, which contributes to the economic burden on health care. The distribution of psoriasis medication costs and the quality of life in these patients has been estimated to be around 20% of total costs.ObjectivesTo estimate the economic distribution of medications and the impact of multiple treatment options on a patient’s quality of life.Materials and methodsThe study was based on 236 Finnish psoriasis patients. The Finnish Social Insurance Institution had databases for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
1
10
0
1
Order By: Relevance
“…lab cost) and arbitrarily levied NB‐UVB charges that are not inherent treatment costs but rather form part of an overall profitable pricing structure. Another Finnish‐based real‐world study from 2009 assigned €39 per annum to methotrexate and €351 per annum to acitretin, but did not quantify NB‐UVB cost, despite stating that this was applied to 36% of patients …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…lab cost) and arbitrarily levied NB‐UVB charges that are not inherent treatment costs but rather form part of an overall profitable pricing structure. Another Finnish‐based real‐world study from 2009 assigned €39 per annum to methotrexate and €351 per annum to acitretin, but did not quantify NB‐UVB cost, despite stating that this was applied to 36% of patients …”
Section: Discussionmentioning
confidence: 99%
“…Another Finnish-based real-world study from 2009 assigned €39 per annum to methotrexate and €351 per annum to acitretin, but did not quantify NB-UVB cost, despite stating that this was applied to 36% of patients. 16 One recent review based in the U.S.A. assigned a direct treatment cost of office-based NB-UVB as ranging between $1414 and $6676 per course based on three cited studies. However, these figures were compiled based on estimates, rather than actual costs, and did not attempt to explain the huge variability in the cited studies.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, patients receiving systemic treatment or phototherapy have been found to have lower PASI values than other patients [ 8 ], possibly due to successful control of psoriasis in patients receiving adequate treatment. In the authors’ previous work [ 27 ] topical therapies were most often combined with other forms of treatment. More severe psoriasis patients, who receive systemic medications to control their symptoms, may need more extensive self-care than those who manage with less care, irrespective of PASI values.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is a chronic immune-mediated skin disease with complex genetic architecture that affects approximately 2% of the world population. It presents a significant economic burden for affected individuals and for society 1 , and can severely impact the patient’s quality of life 2 . Aided by advances in high throughput genotyping technologies, genomewide association studies have identified multiple genetic loci associated with psoriasis 3 6 .…”
Section: Introductionmentioning
confidence: 99%